SNOWDROP SPECIES (GALANTHUS L.): HISTORY OF MEDICAL USE, TOPICAL STANDARDIZATION ISSUES OF HOMEOPATHIC CRUDE HERBAL DRUGS AND MEDICINES BASED ON IT - D. O. Bokov; I. A. Samylina (Разработка и регистрация лекарственных средств, 2019)
Today studies related with development of particular pharmacopoeia monograph for the Homeopathic Pharmacopoeia of the Russian Federation are especially relevant. Particular pharmacopoeia monographs regulate the requirements for homeopathic crude herbal drugs and homoeopathic mother tinctures. In the article the history of snowdrops use in classical medicine and homeopathy is presented. Modern standardization problems of homeopathic crude herbal drugs and homoeopathic mother tinctures produced from Voronov’s snowdrop (Galanthus woronowii Losinsk.) and common snowdrop (Galanthus nivalis L.) are considered.